Mutant P53 expression in chronic myeloid leukemia - Kadhom, Areej E.; Al-Shammari, Haider H. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Chronic Myeloid Leukemia (CML) occurs due to malignant transformation of a pluripotent stem cell. Progression is insidious from chronic to aggressive accelerated or blastic phases. Studies revealed a significant role of the tumor suppressor gene P53 in disease progression. Objectives: To evaluate the immunohistochemical expression of mutant P53 protein in CML at different clinical phases. J Fac Med Baghdad 2013; Vol.55, No .3 Received Nov .2012 Accepted July.2013 Subjects, materials and methods: This case - control study was conducted over 8 months period from January to August in 2010 on 60 preserved bone marrow trephine biopsies of patients with CML (30 in chronic phase, 15 in accelerated phase and 15 in blastic phase) collected from the Department of Histopathology, Teaching laboratories, Medical City directorate, Baghdad. Mutant P53 was evaluated by immunohistochemistry technique of Dakopatts Corporation and scored in the department of pathology / college of medicine / University of Baghdad. Results: This study was done on 60 CML patients whose age mean was 41.6 ± 16.8 years and range from 14 to 81 years with male to female ratio of 1.06:1. Positive mutant P53 expression was detected in 10 out of 30 cases (33.3%) in chronic phase while it was positive in 8 out of 15 cases (53.3%) in the accelerated phase and positive in 13 out of 15 cases (86.7 %) in the blastic phase with p value of 0.003. Conclusions: There was a significant difference in the immunohistochemical expression of mutant P53 in the bone marrow biopsies of CML patients among different phases and its expression was more in advance phases of the disease. Moreover the mutant P53 expression show a significant correlation with the blast percentage in the accelerated and blastic phases of CML.